The Role of Mu'Allim and Mu'Allimah in Building the Morals of Mahasantri Ma'Had Al-Jami'Ah UIN Raden Intan Lampung - Andini, Resti; Patimah, Siti; Bedi, Firman; MasAyu, Sovia; Junaidah, Junaidah (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Ma'had Al-Jami'ah as an educational institution plays an important role in fostering Islamic morals. Mu'allim and Mu'allimah have the obligation to develop students to have good morals at Ma'had Al-Jami'ah Universitas Islam Negeri Raden Intan Lampung. The aim of the research is to find the Mu'allim and Mu'allimah program in developing the morals of students. The research uses a qualitative research approach with a phenomenological design. The research focuses on Mu'allim and Mu'allimah and students to find out the role of Kyai in developing the morals of students at Ma'had Al-Jami'ah Universitas Islam Negeri Raden Intan Lampung. Data collection steps through observation, interviews and documentation. Analysis with data reduction, data display, and data verification. Research results: The results of moral development at Ma'had Al-Jami'ah Universitas Islam Negeri Raden Intan Lampung have shown good changes, especially the morals of students who can be formed, although not all students can show this. As for the students who still have bad behavior, they are based on a life of promiscuity before entering the Islamic boarding school, as a result, some students find it difficult to comply with the rules/orders made by the ma'had aljami'ah Universitas Islam Negeri Raden Intan Lampung.